2005
DOI: 10.1089/end.2005.19.1009
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Holmium Laser Lithotripsy for Impacted Urethral Calculi

Abstract: Intracorporeal intraurethral holmium lasertripsy is a feasible, safe, and effective minimally invasive alternative for the treatment of impacted male urethral calculi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 7 publications
1
13
0
2
Order By: Relevance
“…These infections can occur with recurrent episodes of cystitis or urethritis and can cause life-threatening clinical conditions such as sepsis and penile gangrene [ 9 ]. In many clinical trials, the most common complaint of urethra stones was reported to be acute urinary system retention in accordance with our results [ 4 ]. On the other hand, urinary tract infection was detected in 58.1% of our cases.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These infections can occur with recurrent episodes of cystitis or urethritis and can cause life-threatening clinical conditions such as sepsis and penile gangrene [ 9 ]. In many clinical trials, the most common complaint of urethra stones was reported to be acute urinary system retention in accordance with our results [ 4 ]. On the other hand, urinary tract infection was detected in 58.1% of our cases.…”
Section: Discussionsupporting
confidence: 92%
“…Urethral stones are the rarest among all urinary tract stones and their clinical reflections vary widely. Patients can present to clinics with many different symptoms such as acute urinary retention, weak stream, frequent urination, hematuria, urethrorrhagia, dysuria, a mass in the penis and pain in the penile, rectal or perineal region [ 4 , 9 ]. Another reflection of urethral stones is urinary tract infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stones in the posterior urethra may be manipulated into the urinary bladder followed by cystolithopaxy. When one fails to push the stone back into the urinary bladder in situ fragmentation by holmium laser is also a feasible option if the facility is available 5. US lithotripsy for removal of UC in urethral diverticulum has also been described 6.…”
Section: Discussionmentioning
confidence: 99%
“…Intracorporeal intraurethral Holmium:YAG laserlithotripsy has shown to be a feasible, safe and effective minimally invasive treatment for impacted male urethral and seminal-vesicle stones [36,37].…”
Section: Introductionmentioning
confidence: 99%